Implicações do polimorfismos VAL158 MET da catecol-o-metiltransferase em diferentes aspectos da cognição numérica - Annelise Julio Costa (2014)
The study of val158met catechol-o-methyltransferase (COMT) polymorphism and its relationship to cognitive and emotional measures is growing however the literature on the area with children sample is scarce. This dissertation investigated the influence of this polymorphism on numerical cognition and the underlying mechanisms of mathematical learning. First, an integrative review aimed to identify whether COMT genetic variation in children and adolescents causes differences in performance of working memory tasks. Although negative, the result is not conclusive, since there is no consistency on the analysis of other variables that influence the relationship between COMT and working memory. Subsequently, an experimental study researched how the COMT polymorphism could act on underlying mechanisms learning of mathematics (working memory, transcoding and number sense) in children aged 8 to 12 years-old. The results revealed no differences regarding working memory tasks, however children group with at least one methionine allele demonstrated statistically superior than children group who are homozygous for the valine allele in performance of symbolic non-symbolic numerical tasks. These evidences suggest COMT-related dopaminergic modulation may be related to magnitude processing. Finally, we investigated how emotional aspects of mathematical learning may be influenced by the COMT polymorphism in children aged 7-12 years-old. It was observed that male children with val158val genotype showed lower levels of math anxiety compared to children with at least one methionine allele. Furthermore, the COMT genotype along with other emotional factor (unhappiness related to problems in mathematics) and grade were predictors of math anxiety in males, while for girls model the genetic variable was not statistically significant. In general, data from this dissertation corroborate to literature by pointing cognitive advantages for methionine allele and better emotional regulation for the valine allele, but it also innovates to demonstrate dopaminergic influences, operationalized by the val158met COMT polymorphism on numerical cognition and its underlying mechanisms. Studies are still exploratory, however when we investigate genetic influences of numerical cognition it raises theoretical questions with implications both for understanding genetic mechanisms of mathematical learning and possible etiological factors for the developmental dyscalculia.